Influence of defect luminescence and structural modification on the electrical properties of Magnesium Doped Zinc Oxide Nanorods. (June 2017) - Santoshkumar, B.; Biswas, Amrita; Kalyanaraman, S.; Thangavel, R.; Udayabhanu, G.; Annadurai, G.; Velumani, S.
Abstract: Magnesium doped zinc oxide nanorod arrays on zinc oxide seed layers were grown by hydrothermal method. X-ray diffraction (XRD) patterns revealed the growth orientation along the preferential (002) direction. The hexagonal morphology was revealed from the field emission scanning electron microscope (FESEM) images. The elemental composition of the samples was confirmed by energy dispersive x-ray analysis spectra (EDS) and mapping dots. Carrier concentration, resistivity and mobility of the samples were obtained by Hall measurements. I-V characteristic curve confirmed the increase in resistivity upon doping. Photoluminescence (PL) spectra exposed the characteristic of UV emission along with defect mediated visible emission in the samples. Electrochemical impedance spectroscopy and cyclic voltammetry were undertaken to study the charge transport property. Owing to the change in the structural parameters and defect concentration the electrical properties of the doped samples were altered. Highlights: Attempt to probe the electrical properties of pure and Mg doped ZnO nanorods. Oxygen interstitial might be responsible for the defect emission observed in Photoluminescence spectra. Smaller pore structure and reduced specific surface area of the MgZnO nanorod electrodes. Capacitive behaviour due to redox mechanism observed in cyclic voltammetry. Diminished interfacial charge transfer in between MgZnO nanorods and oxide-electrolyte interface.